Perjanjian Tambahan 1905/1906 Brunei dan United Kingdom: Satu Tinjauan Hubungannya dengan Undang-Undang Tanah - Haji Mail, Haji Awg Asbol bin (SOSIOHUMANIKA, 2009)
ABSTRACT: The system of British Resident government was introduced in Brunei on early twenteeth century. By implementing this system, Brunei is one of nation in Southeast Asian countries which be ruled by British indirectly. Similar with other British ruled regions in Southeast Asia, especially to Malay peninsulaâs case, the Sultanate of Brunei has also to receive the advises on social, economic and political matters from British Resident. Exceptly is concerning on the Islamic religion matters. As its consequences, the Brunei faced the changes not only in social, political and economic field but also in management of government and in regulation of Land Code. The later case indicates that regulating on land in Brunei traditionally was also changed by modern Land Code respectively in early twentieth century. However, this paperwork tries to explain how the signing of 1905/1906 Supplementary Agreement resulted in the formulation of Land Code 1907. The signing of this agreement shows that the British were concerned with Bruneiâs survival which was very much affected by the land issues in Brunei. With the Land Code 1907, the boundaries of the Sultanate were made clear and subsequently played its roles in improving and sustaining Bruneiâs economy. In one way or another, the Land Code was responsible for increasing in revenue through income from rubber plantation, and oil and gas industry. Thus, it acts as a catalyst for the development in Brunei and Brunei was able to transform from an economically unstable country to a country which is blessed with prosperity. All of these achievements are achieved due to the endless effort of the government in implementing the Land Code in Brunei. Key words: Brunei Sultanate, British Resident government, Land Code of 1907, and political, economic and social changes in Brunei.About the Author: Dr. Haji Awg Asbol bin Haji Mail ialah Pensyarah Kanan di Jabatan Sejarah, Fakulti Sastera dan Sains Sosial UBD (Universiti Brunei Darussalam). Beliau dilahirkan di Limbang, Sarawak, pada 24hb Disember 1955. Menamatkan pengajian Sarjana Muda (B.A.Hons.) dari Universiti Brunei Darussalam pada tahun 1989; berkelulusan Sarjana (M.A.) dari universiti yang sama pada tahun 1996; dan berkelulusan program Doktor (Ph.D.) dari Universiti Malaya, Kuala Lumpur, Malaysia, pada tahun 2004, dengan menulis disertasi mengenai âKesultanan Brunei Abad ke-19: Sistem Politik dan Struktur Pentadbiranâ. Beliau menulis beberapa buku, di antaranya adalah Sejarah Perkembangan Pendidikan di Brunei, 1950-1985 (Brunei Darussalam: Jabatan Pusat Sejarah Brunei, 2006). Bagi urusan sebarang akademik, beliau dapat dihubungi dengan alamat e-mail: asbolm@fass.ubd.edu.bn atau asbolm@hotmail.comÂ Â Â How to cite this article? Haji Mail, Haji Awg Asbol bin. (2009). âPerjanjian Tambahan 1905/1906 Brunei dan United Kingdom: Satu Tinjauan Hubungannya dengan Undang-Undang Tanahâ in SOSIOHUMANIKA: Jurnal Pendidikan Sains Sosial dan Kemanusiaan, Vol.2, No.1 [Mei], pp.31-46. Bandung, Indonesia: Minda Masagi Press, UPI Bandung, and UMS Kota Kinabalu, Malaysia, ISSN 1979-0112. Chronicle of article: Accepted (March 8, 2009); Revised (April 12, 2009); and Published (May 20, 2009).